Biomechanical Properties of Double- and Single-Row Suture Anchor Repair for Surgical Treatment of Insertional Achilles Tendinopathy. (July 2013) - Beitzel, Knut; Mazzocca, Augustus D.; Obopilwe, Elifho; Boyle, James W.; McWilliam, James; Rincon, Lina; Dhar, Yasmin; Arciero, Robert A.; Amendola, Annunziato
Background: Because of intratendinous ossifications, retrocalcaneal bursitis, or intratendinous necrosis commonly found in insertional tendinosis, it is often necessary to detach the tendon partially or entirely from its tendon-to-bone junction. Hypothesis: Double-row repair for insertional Achilles tendinopathy will generate an increased contact area and demonstrate higher biomechanical stability. Study Design: Controlled laboratory study. Methods: Eighteen cadaver Achilles tendons were split longitudinally and detached, exposing the calcaneus; an ostectomy was performed and the tendon was reattached to the calcaneus in 1 of 2 ways: 2 suture anchors (single row) or a 4-anchor (double row) construct. Footprint area measurements over time, displacement after cyclic loading (2000 cycles), and final load to failure were measured. Results: The double-row refixation technique was statistically superior to the single-row technique in footprint area measurement initially and 5 minutes after repair ( P = .009 and P = .01, respectively) but not after 24 hours ( P = .713). The double-row construct demonstrated significantly improved measures for peak load (433.9 ± 84.3 N vs 212.0 ± 49.7 N; P = .042), load at yield (354.7 ± 106.2 N vs 198.7 ± 39.5 N; P = .01), and slope (51.8 ± 9.9 N/mm vs 66.7 ± 16.2 N/mm; P = .021). Cyclic loading did not demonstrate significant differences between the 2 constructs. Conclusion: Double-row construct for reinsertion of a completely detached Achilles tendon using proximal and distal rows resulted in significantly larger contact area initially and 5 minutes after repair and led to significantly higher peak load to failure on destructive testing. Clinical Relevance: In treatment for insertional Achilles tendinosis, the tendon often has to be detached and anatomically reattached to its insertion at the calcaneus. To our knowledge there is a lack of biomechanical studies supporting either a number or a pattern of suture anchor fixation. Because the stresses going across the insertion site of the Achilles tendon are significant during rehabilitation and weightbearing activities, it is imperative to have a strong construct that allows satisfactory healing during the early postoperative process.